Pejabat Ahli Parlimen Malaysia P.218 Sibuti / Al-Nadzirul Mubin Arbi - Arbi, Al-Nadzirul Mubin (Universiti Teknologi MARA, Sarawak, 2015)
The Member of Parliament’s Office is directly administered by the MP for that particular constituency. This organization is being established in order for the MP to perform and give services toward the public efficiently. The vision of this organization is to become the pioneer and benchmark to other local and international legislative institutions. The Mission of the organization is to give quality service to the clients and to apply the best and strategic practice for resources management and administration of the organization. Other than that, the organization also committed to efficiently fulfil the responsibilities towards the stakeholders. The motto for this organization is Berkorban, Bersatu and Memimpin Pendapat Rakyat. These mottos are reflecting the initiative of the MP in delivering services and protecting the welfare of the public. The core business of the organization is more or less similar with the functions of a government agency. This organization concern on serving the people based on their needs and demands. There are about thirteen employees who work in the organization and each of the employees is having their own scope of job. This organization consists of 2 floors and located at Jalan Datuk Muip, Piasau Jaya Miri Sarawak.